2021
DOI: 10.3390/su13105594
|View full text |Cite
|
Sign up to set email alerts
|

Do Environmental Transformational Leadership Predicts Organizational Citizenship Behavior towards Environment in Hospitality Industry: Using Structural Equation Modelling Approach

Abstract: Voluntary pro-environmental behaviors in the workplace such as organizational citizenship behavior towards environment (OCBE) are pertinent for the organizations striving to become environmentally responsible entities. The significance of OCBE for green organizational initiatives has led scholars to strive for expanding its nomological network. Approaching from the theoretical angle of the social information processing approach, this quantitative, survey-based study theoretically links and empirically tests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 135 publications
0
27
0
1
Order By: Relevance
“…Prior research has shown that green transformational leadership is positively related to organizational citizenship behavior [ 7 ] and organizational citizenship behavior for the environment [ 8 , 9 ]; however, as we mentioned above, employees’ taking charge behavior is different from organizational citizenship behavior in several aspects. Organizational citizenship behavior places more emphasis on affiliative behaviors such as helping, sharing, and cooperating, which is the modest behavior that sustains the status quo [ 24 ].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Prior research has shown that green transformational leadership is positively related to organizational citizenship behavior [ 7 ] and organizational citizenship behavior for the environment [ 8 , 9 ]; however, as we mentioned above, employees’ taking charge behavior is different from organizational citizenship behavior in several aspects. Organizational citizenship behavior places more emphasis on affiliative behaviors such as helping, sharing, and cooperating, which is the modest behavior that sustains the status quo [ 24 ].…”
Section: Introductionmentioning
confidence: 93%
“…Green transformational leadership, which is also called environmental transformational leadership, is a leadership style that aims to motivate employees to achieve green goals, shape the green vision of employees and promote green change in the organization [ 5 ]. Previous research on green transformational leadership has illustrated its profound impact on employees’ environmental responsibility [ 6 ], organizational citizenship behavior [ 7 ], organizational citizenship behavior for the environment [ 8 , 9 ], and its importance for sustainable development at the organizational level [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature Review and Developing the Hypotheses Environmentally Specific Servant Leadership and Employees' Pro-Environmental Behavior During the last decade, a shift in the focus of leadership studies has been started towards environmental issues, [23][24][25] and environmentally specific constructs of various leadership styles have emerged. [26][27][28][29] To date, environmentally specific or green transformational leadership attracted a significant share of studies predicting its influence on employees' environment-related behaviors. However, only recently, Tuan (2018) conceptualized environmentally specific servant leadership that has started attracting researchers' in this area.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…At the same time, more opportunities for job performance and autonomy should be given to employees, which can help employees recognize the organization's attention and cultivation. 57 As a result, the sense of belonging and affective attachment to the organization will be improved for employees and promote the implementation of OCB.…”
Section: Management Implicationsmentioning
confidence: 99%